2020
DOI: 10.1007/s10811-020-02103-6
|View full text |Cite
|
Sign up to set email alerts
|

Composition analysis and minimal treatments to solubilize polysaccharides from the brown seaweed Laminaria digitata for microbial growth of thermophiles

Abstract: Brown macroalgae (Phaeophyta) hold high potential as feedstock for biorefineries due to high biomass productivity and carbohydrate content. They are, however, a challenging, unconventional feedstock for microbial refining and several processing problems need to be solved to make them a viable option. Pre-treatment is necessary to enhance accessibility and solubility of the biomass components but should be minimal and mild to assure sustainable and cost-effective processing. Here, two routes to pre-treatLaminar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Focused windows (in specific wavenumber ranges) are reported in Figure S3 (see Supplementary Materials) . Brown algal biomass ( L. digitata ) contains an important alginate: based on the literature, this fraction may reach up to 50% [ 55 ], although this composition may vary with location and season [ 56 , 57 ]. This fraction of alginate is partially extracted by sodium carbonate with heating and may be available for further reaction with other constituents of the sorbent.…”
Section: Resultsmentioning
confidence: 99%
“…Focused windows (in specific wavenumber ranges) are reported in Figure S3 (see Supplementary Materials) . Brown algal biomass ( L. digitata ) contains an important alginate: based on the literature, this fraction may reach up to 50% [ 55 ], although this composition may vary with location and season [ 56 , 57 ]. This fraction of alginate is partially extracted by sodium carbonate with heating and may be available for further reaction with other constituents of the sorbent.…”
Section: Resultsmentioning
confidence: 99%
“…A L PEI beads naturally contains sulfur due to the presence of fucoidan in the wall of L. digitata [67 68]; however, the biopolymer fraction (which depends on seasonal variations, part of the algae, collect location, etc.) remains very low in the raw support [69]. The functionalization of the beads increased the content from 0.32% (i.e., 0.100 mmol S g −1 ) to 3.08% (i.e., 0.961 mmol S g −1 ).…”
Section: Elemental Analysismentioning
confidence: 99%
“…As an alternative to increasing the amount of SWE to increase the concentration of carbon source, the extract could potentially be used as a source of minerals and micronutrients in fermentation (Sharma et al, 2018). In a study by Allahgholi et al (2020), B. methanolicus MGA3 was cultivated on extracts of the alternative seaweed Laminaria digitata. In that study, it was found that reducing the concentration of the SWE and supplementing the culture with extra mannitol, resulted in higher biomass formation than when the strain was cultivated on a reference medium without SWE, and with mannitol as sole carbon source.…”
Section: Discussionmentioning
confidence: 99%